Legal Analysis of The Application of Islamic Economic Principles in International Trade Law to Realize Fair World Economic Development - Helza Nova Lita; Norazlina Abdul Azis; Adnan Mahmutovic (Universitas Lampung, 2025)
The current international trade law tends to promote competition rather than cooperation, often leading to conflicts between parties to the agreement. The general principles underlying the agreement between parties in international trade law can be related to Islamic economic principles. The GATT and WTO treaties aim to regulate all sectors of global trade as they evolve, encompassing significant developments in international trade, particularly trade among countries with a Muslim majority population. Essentially, Islamic Agreement Law adheres to the principle of freedom of contract, as outlined in the provisions of the Lex Mercatoria and the Civil Code. Thus, the role of individuals in the agreement becomes crucial to understanding the value of the principle of freedom of contract, which is closely related to the principle of party consent. This article offers explanations and solutions to address the primary issues in current international trade agreement practices, grounded in the principles of Islamic Economics. The analytical study will use normative juridical methods and Islamic law. The concept of Islamic Economics is overly concerned with the balanced protection of the parties. In its strategic position, Islamic economic principles can be applied in international trade cooperation relations not only in countries where most of the population is Muslim, but also in Muslim minority countries.